2012
DOI: 10.1007/s10856-012-4574-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the cytotoxic and inflammatory responses of titanium particles with different methods for endotoxin removal in RAW264.7 macrophages

Abstract: It is generally accepted that periprosthetic bone resorption is initiated through aseptic inflammation aggravated by wear particles that are generated from artificial joint. However, some studies have demonstrated that "endotoxin-free" wear particles are almost completely unable to stimulate the macrophage-mediated production of proinflammatory cytokines. Here, we compare the titanium particles with different methods of endotoxin removal. The results indicated that different titanium particle preparation dosag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 45 publications
(53 reference statements)
1
14
3
Order By: Relevance
“…A previous study showed that cytokine production and osteoclast differentiation are stimulated by endotoxins that adhere to wear particles [34] . Furthermore, LPS treatment of titanium particles increased TNF-α and IL-1β production in THP-1 cells [35] .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that cytokine production and osteoclast differentiation are stimulated by endotoxins that adhere to wear particles [34] . Furthermore, LPS treatment of titanium particles increased TNF-α and IL-1β production in THP-1 cells [35] .…”
Section: Discussionmentioning
confidence: 99%
“…Wear particles have been known to have high affinity for endotoxin [70,71] which may allow systemic endotoxin to bind to generated wear particles. Furthermore, endotoxin in subclinical concentrations of bacteria have been demonstrated to be present on implants and wear particles [43].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that cytokine production and osteoclast differentiation are stimulated by adherent endotoxins on wear particles [37]. Therefore, our discs were disinfected using autoclave and tested for endotoxins to ensure that the discs were free of contamination.…”
Section: Discussionmentioning
confidence: 99%